Hydrologic‐Economic Trade‐offs in Groundwater Allocation Policy Design. Issue 1 (20th January 2021) - Young, Richael; Foster, Timothy; Mieno, Taro; Valocchi, Albert; Brozović, Nicholas
Abstract: A common environmental externality of groundwater pumping is streamflow depletion. To manage impacts of groundwater pumping on hydrologically connected surface water systems, regulators often impose quotas, or allocations, limiting the rates of groundwater extraction. Allocations vary in their temporal flexibility, ranging from single‐year "hard caps" to multi‐year "soft caps". Soft cap allocations allow greater flexibility for farmers, the primary users of groundwater, to adjust irrigation rates from one year to another, potentially providing greater resilience to drought but also altering hydrologic impacts of pumping. In this study, we integrate agronomic, economic, and hydrologic models to evaluate optimal irrigation decisions for a range of equivalent hard and soft cap limits, and assess trade‐offs between the resulting economic (farm profitability) and hydrologic (stream depletion) outcomes. Soft cap allocation policies consistently outperform equivalent hard caps in terms of greater farm profitability and reduced production risks. However, the economic benefits of soft caps come at the cost of higher peak and cumulative rates of streamflow depletion, with the magnitude of differences dependent on aquifer properties, well location, and the length of the soft cap allocation period. Our findings suggest that the optimal allocation design will depend on competing socioeconomic and environmental objectives, and, in some instances, may require a blended approach to efficiently achieve desired management goals. Key Points: We examine the trade‐offs of alternative groundwater allocation policies on farm profitability and stream depletion Multi‐year allocations smooth income and reduce water‐related production risk but cause higher stream depletion than single‐year allocations Trade‐offs between single‐year and multi‐year allocations increase for longer allocation periods and wells closer to streams